Current Trends in Education for the Translation Profession – Pilot Study on Student Population in Croatia - Seljan, Sanja (2001)
Education for the translator's profession in accession country, such as Croatia, requires, besides regular knowledge and skills, readiness for further education and awareness of necessity for building of new compatible language resources. The research presents interests and use of language technology resources at the Department of Information Sciences, Faculty of Humanities and Social Sciences in Zagreb. Since most of students study information sciences and languages, the research presents their interests in translation, evaluation of language resources and interest for future education as translator’s specialist.